2012
DOI: 10.1097/aap.0b013e31825cb3d6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Local Anesthetic Systemic Toxicity and Postoperative Neurologic Symptoms Associated With 12,668 Ultrasound-Guided Nerve Blocks

Abstract: In the setting of a surgical procedure, ultrasound-guided regional anesthesia is associated with the risk of long-term postoperative neurologic symptoms. Local anesthetic systemic toxicity, however, is extremely uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
124
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(132 citation statements)
references
References 14 publications
3
124
3
2
Order By: Relevance
“…Others 21 support that the insertion of ultrasound-guided stimulating catheters requires the administration of lower amounts of local anesthetic. -After evaluating 12,688 patients over 8 years, Sites et al 22 observed a low incidence of systemic toxicity (0.08/1000) and postoperative neurologic symptoms (0.9/1000) lasting greater than 6 months after having performance ultrasound-guided peripheral nerve blocks. Such low systemic toxicity incidence is even lower than that verified by Barrington et al 23 and Orebaugh et al 24 in their separate studies, which was already low enough.…”
Section: Neurostimulation In Peripheral Nerve Blocksmentioning
confidence: 97%
“…Others 21 support that the insertion of ultrasound-guided stimulating catheters requires the administration of lower amounts of local anesthetic. -After evaluating 12,688 patients over 8 years, Sites et al 22 observed a low incidence of systemic toxicity (0.08/1000) and postoperative neurologic symptoms (0.9/1000) lasting greater than 6 months after having performance ultrasound-guided peripheral nerve blocks. Such low systemic toxicity incidence is even lower than that verified by Barrington et al 23 and Orebaugh et al 24 in their separate studies, which was already low enough.…”
Section: Neurostimulation In Peripheral Nerve Blocksmentioning
confidence: 97%
“…The largest review to date showed a rate of procedural paresthesia in 2.0% and transient neurologic deficit lasting 5 days to 6 months in 1.9% of patients. 137 The ultrasound machine is positioned opposite the provider with the patient supine and the leg slightly abducted. Using a linear probe, the landmarks of femoral nerve, femoral artery, vein, and fascia lata and iliaca should be identified.…”
Section: Peripheral Nerve Blockadementioning
confidence: 99%
“…Se hace especial hincapié en revisar la historia clínica y corroborar la toma de anticoagulantes o HBPM, ya que estas prácticas siguen suponiendo un riesgo a pesar de las numerosas revisiones y guías clínicas realizadas por la ASRA y ASA. Debe revisarse y disponer de las principales drogas utilizadas en caso de RCP, y particularmente la disponibilidad de la emulsión lipídica para el tratamiento de una posible toxicidad por AL, cuya ratio de presentación oscila en torno a 1:2000 técnicas locorregionales (22).…”
Section: Propuesta De Checklist En Bloqueos Regionales De La Asraunclassified